2007
DOI: 10.1016/j.febslet.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid in the PSPG‐box plays an important role in the catalytic function of CaUGT2 (Curcumin glucosyltransferase), a Group D Family 1 glucosyltransferase from Catharanthus roseus

Abstract: Curcumin glucosyltransferase (CaUGT2) isolated from cell cultures of Catharanthus roseus exhibits unique substrate specificity. To identify amino acids involved in substrate recognition and catalytic activity of CaUGT2, a combination of domain swapping and site-directed mutagenesis was carried out. Exchange of the PSPG-box of CaUGT2 with that of NtGT1b (a phenolic glucosyltransferase from tobacco) led to complete loss of enzyme activity in the resulting recombinant protein. However, replacement of Arg378 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…By domain swapping between two GTs of 85% identity, Brazier-Hicks et al (5) found a region of five variable amino acids responsible for enabling the formation of N-glucosides in addition to O-glucosides. Other studies (30,31) found that at lower levels of sequence identity (75 and 28%, respectively) the generated chimeras were inactive.…”
Section: Discussionmentioning
confidence: 99%
“…By domain swapping between two GTs of 85% identity, Brazier-Hicks et al (5) found a region of five variable amino acids responsible for enabling the formation of N-glucosides in addition to O-glucosides. Other studies (30,31) found that at lower levels of sequence identity (75 and 28%, respectively) the generated chimeras were inactive.…”
Section: Discussionmentioning
confidence: 99%
“…The changes were explained by changed size of the acceptor pocket resulting from introduction of smaller amino acid side chains, allowing for different positioning of the acceptor molecules (He et al, 2006). Change in the size of a single amino acid residue has also been observed to alter acceptor specificity of other plant UGTs (Masada et al, 2007;Cartwright et al, 2008). Eight other point mutations in the acceptor pocket of MtUGT71G1 resulted in activities of 20% to 90% of wild-type protein (He et al, 2006).…”
Section: Sugar Acceptor Specificity Of Bpugt94b1mentioning
confidence: 99%
“…A previous study reported that a nonconserved residue, Cys-377, in the PSPG-box of CaUGT2 plays an essential role in determining the catalytic function of CaUGT2 (Masada et al, 2007). In this study, we have shown that the D343E, K458R, and D445E single mutants and the G433A/I434V double mutant of UGT71A33 all displayed enhanced HDMF glucosylation activity, particularly the D343E mutant and G433A/I434V double mutant, which exhibited increases in activity more than 2-fold above that of the wild-type enzyme UGT71A33 (Fig.…”
Section: Site-directed Mutagenesis Identified Residues Important For mentioning
confidence: 99%